2020
DOI: 10.1371/journal.pone.0242857
|View full text |Cite
|
Sign up to set email alerts
|

Applications of EEG indices for the quantification of human cognitive performance: A systematic review and bibliometric analysis

Abstract: Background Neuroergonomics combines neuroscience with ergonomics to study human performance using recorded brain signals. Such neural signatures of performance can be measured using a variety of neuroimaging techniques, including functional magnetic resonance imaging (fMRI), functional near-infrared spectroscopy (fNIRS), and electroencephalography (EEG). EEG has an excellent temporal resolution, and EEG indices are highly sensitive to human brain activity fluctuations. Objective The focus of this systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 218 publications
1
35
0
Order By: Relevance
“…A drawback of the SPA technique is that the analysis provides only an average change in frequency over a given time period, which fails to utilise the most important benefit of EEG measurements, namely an excellent temporal resolution [ 59 ]. Studies investigating the effect of MF on ERP values are scarce, but are possibly more important in the search for explanations behind MF mechanisms as ERPs represent an immediate change in brain activity due to a task stimulus [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of the SPA technique is that the analysis provides only an average change in frequency over a given time period, which fails to utilise the most important benefit of EEG measurements, namely an excellent temporal resolution [ 59 ]. Studies investigating the effect of MF on ERP values are scarce, but are possibly more important in the search for explanations behind MF mechanisms as ERPs represent an immediate change in brain activity due to a task stimulus [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in alpha power is found in certain conditions such as fatigue and dizziness; in particular, a recent review summarizes power spectral density changes especially in the alpha spectrum in different vigilance and general conditions (Ismail and Karwowski, 2020). Therefore, it must be argued that changes in frequency power are due to reduced vigilance because of exertion in the VR environment.…”
Section: Effects Of Dizziness and Drowsinessmentioning
confidence: 99%
“…In addition, the mean relaxation score in the experimental condition was significantly higher than that in the control condition. Alpha waves are known to be correlated with decreased mental stress, increased relaxation, and enhanced memory ability ( Alarcao and Fonseca, 2017 ; Lina and Karwowski, 2020 ). Further, several reports have shown that exposure to the natural environment induces increased alpha wave strength, which is related to physiological relaxation and recovery effects ( Kim et al, 2013 , p. 38; Alarcao and Fonseca, 2017 ; Ursuţiu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some scholars have proposed a new research method in which brain waves are used to represent emotional state ( Niedermeyer and Silva, 2004 ). Electroencephalogram (EEG) refers to the recording of electrical signals of the human brain at a scalp level ( Lina and Karwowski, 2020 ). Under the active brain, the postsynaptic potentials of pyramidal neurons will be hyperpolarized and depolarized, and EEG signals are generated.…”
Section: Introductionmentioning
confidence: 99%